Family law professionals' views of post-separation parenting apps. (8th December 2022) - Payne, Jason L; Smyth, Bruce M; Irving, Michelle; Heard, Genevieve; Althor, Glenn
Abstract: The rapid proliferation of smartphones has led to a bewildering array of post-separation parenting apps, especially since the Covid-19 pandemic. These apps usually comprise a messaging tool, shared calendar, expense tracker, and a means to download messages and documents for courts. In Australia, as elsewhere, family law professionals are increasingly being asked about, or asked to recommend, smartphone apps to clients. There is also an emerging trend for courts to mandate the use of post-separation parenting apps in high conflict cases. The present study sought to explore the views and experiences of family law professionals on post-separation parenting smartphone apps (N = 344). Data were collected in Australia and New Zealand through an online survey, distributed to a diverse population of family law professionals. We found that (i) family law professionals generally reported little knowledge of co-parenting apps; (ii) around one third of family law professionals reported that their clients had experienced, or concerns about, coercive control through an app; (iii) around two thirds of family law professionals who had recommended an app had not tried it; and yet (iv) three quarters reported recommending apps to clients. Our central argument is that family law professionals and separated parents alike need a comprehensive and more nuanced understanding of the benefits and risks of post-separation parenting apps and their features.